Predicting fungal community dynamics driven by competition for space. (October 2019) - Kolesidis, Danis A.; Boddy, Lynne; Eastwood, Daniel C.; Yuan, Chenggui; Fowler, Mike S.
Abstract: Predicting fungal community dynamics requires methods combining theory with experiments. Different elements of spatial competition influence interaction outcomes, and consequently community dynamics. Despite the literature on such elements, no theoretical study has tested the predictability of dynamics with models incorporating these elements. We aimed to develop a method for predicting dynamics, to be tested first under laboratory conditions. Six spatial competition elements were quantified for three basidiomycete species on agar. We found: constant extension; extension unaffected by other mycelia; faster replacement of younger mycelial regions; faster replacement of smaller mycelia; uniform distribution of mycelial competitive ability across the boundary with heterospecifics; and additive effects of competition. We developed a lattice model, and found that incorporation of all experimentally quantified elements was necessary for accurate prediction of dynamics. Our study provides a methodological basis for prediction of fungal dynamics, and hence of ecosystem processes in which filamentous fungi are key players.